Haploid-inducer development by CRISPR/Cas9 mediated CenH3 gene modification in Helianthus annuus (Sunflower) - Crampton, Bridget Genevieve (University of Pretoria, 2023)
Thesis (PhD (Biotechnology))--University of Pretoria, 2023.